Multiset Controlled Grammars: A Simple Method in Regulated Rewriting Theory - Salbiah Ashaari; Sherzod Turaev; M. Izzuddin M. Tamrin; Abdurahim Okhunov; Tamara Zhukabayeva (Institute of Advanced Engineering and Science, 2017)
This study focus on defining a new variant of regulated grammars called multiset controlled grammars as well as investigating their computational power. We apply a constructive theoretical approach; the intent of which is to provide new theories based on computational methods where the results are appeared in the form of examples, lemmas and theorems. In the study, we have found that multiset is powerful and yet a simple method in regulated rewriting theory. We have proved that multiset controlled grammars are at least as powerful as additive valence grammars, and they are at most powerful as matrix grammars.